Epidemiology of traumatic brain injuries in Europe: a cross-sectional analysis - Marek Majdan, DrPhD; Dominika Plancikova, MSc; Alexandra Brazinova, PhD; Martin Rusnak, ProfPhD; Daan Nieboer, MSc; Valery Feigin, ProfMD; Andrew Maas, ProfMD (The Lancet Public Health, 2016)
Summary: Introduction: Traumatic brain injuries (TBI) are a major medical and socioeconomic problem. We aimed to estimate the hospital-based incidence, population-wide mortality, and the contribution of TBI to injury-related mortalities in European countries, and to provide European summary estimates for these indicators. Methods: For this cross-sectional analysis, we obtained population data from Eurostat for hospital discharges and causes of death in European countries in 2012. Outcomes of interest were TBIs that required hospital admission or were fatal. We calculated age-adjusted hospital discharge rates and mortality rates and extrapolated data to 28 European Union countries and all 48 states in Europe. We present between-country comparisons, pooled age-adjusted rates, and comparisons with all-injury rates. Findings: In 2012, 1 375 974 hospital discharges (data from 24 countries) and 33 415 deaths (25 countries) related to TBI were identified. The pooled age-adjusted hospital discharge rate was 287·2 per 100 000 (95% CI 232·9–341·5) and the pooled age-adjusted mortality rate was 11·7 per 100 000 (9·9–13·6). TBI caused 37% (95% CI 36–38) of all injury-related deaths in the analysed countries. Extrapolating our results, we estimate 56 946 (95% CI 47 286–66 099) TBI-related deaths and 1 445 526 (1 172 996–1 717 039) hospital discharges occurred in 2012 in the European Union (population 508·5 million) and about 82 000 deaths and about 2·1 million hospital discharges in the whole of Europe (population 737 million). We noted substantial between-country differences. Interpretation: TBI is an important cause of death and hospital admissions in Europe. The substantial between-country differences observed warrant further study and suggest that the true burden of TBI in Europe has not yet been captured. Rigorous epidemiological studies are needed to fully quantify the effect of TBI on society. Despite a great degree of consistency in data reporting across countries already being achieved, further efforts in this respect could improve the validity of between-country comparisons. Funding: European Union, FP7.